How to draw Kawaii manga fashion - Misako Rokkusu, 1977- (Misako Rokkusu, 1977- Learn manga with Misako., 2025)
"Attention kawaii and fashion-loving tweens! Now you can learn to draw your own adorable manga fashions with this fun-to-read guide by award-winning middle-grade graphic novelist Misako Rocks! Combining drawing tutorials with motivational messages that encourage artists to draw and think freely, How to Draw Kawaii Manga Fashion inspires kids to unleash their creativity in the most entertaining way possible. This engaging and easy-to-follow book includes: Helpful tips on how to use the book Instructions for drawing kawaii-style accessories, clothing, hairstyles, and more Tips for adding color and shading to bring kawaii fashion creations to life Young artists everywhere will find inspiration in Misako's remarkable story as they follow her warm, accessible instructions in pursuit of their own dreams" --